Structural Connection between Activation Microswitch and Allosteric Sodium Site in GPCR Signaling - White, Kate L.; Eddy, Matthew T.; Gao, Zhan-Guo; Han, Gye Won; Lian, Tiffany; Deary, Alexander; Patel, Nilkanth; Jacobson, Kenneth A.; Katritch, Vsevolod; Stevens, Raymond C. (Structure (London), 2018)
Sodium ions are endogenous allosteric modulators of many G-protein-coupled receptors (GPCRs). Mutation of key residues in the sodium binding motif causes a striking effect on G-protein signaling. We report the crystal structures of agonist complexes for two variants in the first sodium coordination shell of the human A2A adenosine receptor, D522.50N and S913.39A. Both structures present an overall active-like conformation; however, the variants show key changes in the activation motif NPxxY. Changes in the hydrogen bonding network in this microswitch suggest a possible mechanism for modified G-protein signaling and enhanced thermal stability. These structures, signaling data, and thermal stability analysis with a panel of pharmacological ligands provide a basis for understanding the role of the sodium-coordinating residues on stability and G-protein signaling. Utilizing the D2.50N variant is a promising method for stabilizing class A GPCRs to accelerate structural efforts and drug discovery. [Display omitted] •X-ray structures of A2AAR variants D2.50N and S3.39A agonist complexes•A2AAR-D2.50N shows striking loss of G-protein signaling•Structural changes near activation motif correspond to loss of signaling•D2.50N improves GPCR stability for accelerating drug discovery White and Eddy et al. report agonist-bound structures of human A2AAR variants that disrupt allosteric sodium effects. The structures reveal changes in hydrogen bonding near a conserved activation motif that correspond to striking differences in signaling, providing a rationale for increased variant receptor stability.